Nødvendig – Nyttig – Rettferdig? Likestillingsargumenter i offentlig debatt - Skjeie, Hege; Teigen, Mari (Kvinder, Køn & Forskning, 2005)
This article discusses the steadily stronger emphasize on diversity arguments which underscore ‘gender difference’ and diversity’s ‘utility’ as arguments in support of gender equality in Norwegian public debate. In both party political, femocratic and media mediated debates on gender equality, rights-based justifications seem largely to be replaced by a discourse prioritizing utility/profitability arguments. The article provides a series of examples of these strands of arguments in support of gender equality policies, and outlines a set of normative problems connected with the mixture of gender difference and utility based justifications. In contrast, we argue that comprehensions of ‘gender equality’ rather must be based on a principle of rights where understandings of gender differences are restricted to conditions for access: ‘an equal right to equal participation’. This discussion is supplemented with an analysis of attitudinal data from two surveys conducted as part of the Norwegian Power and Democracy Study (1998-2003), a large scale Elite Survey and a corresponding omnibus. One set of questions in both of these surveys asks people how they prioritize between different types of arguments in support of gender equality. The analysis indicates that the ‘diversity pays’ line of argumentation combined with a ‘rhetoric of difference’ mainly receives support on elite levels of Norwegian society.